Blogging 9/11 and Memory Discourse (Altre Modernità, 2011)
Marking ‘Time Zero’ in the history of the US and the world, the 9/11 catastrophe provoked an outburst of discourses that found an unprecedented sounding board in the blogosphere, flooded with fragmentary contributions from a global public that mostly witnessed the event mediated by TV coverage. Examining a decade bracketed by those traumatic attacks and Osama bin Laden’s death, we may ask ourselves in what relationship the continuous flow of comments, disclosures and news updates published on 9/11-related blogs stands to the making of the history of the event and what followed it, especially the emergence of the ‘war-on-terror’ rhetoric.This article highlights a few of the salient discursive and linguistic patterns that recur in the 9/11 narratives that have multiplied online on several dedicated websites and investigates the evolution of 9/11 cultural memory practices, torn between the discourse of the unrepresentable and the imperative to remember. It claims that blogging 9/11, immediately after the attacks and over the years, well illustrates how the logic of memory and its interpretation of the past follow different criteria from history writing. It shows how memorialization practices, dictated by the fear of forgetting the vanishing present, contribute to that excess of memory that lies at the core of the instability and mutual competition of sources retrieved on the Internet and that might ultimately lead to a rethinking of what is the contribution of collective memory to historiography.